HUBUNGAN ANTARA POWER OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI DENGAN PASSING LAMBUNG DALAM PERMAINAN SEPAKBOLA DI SSB RUMBAI FC JUNIOR - Bimanjaya, Panji; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out whether there is a relationship between the power of muscle limbs and the coordination of eyes and feet with gastric passing in soccer games in SSB Rumbai FC junior. The sample from this study was the 16-member Junior High School FC Tassel School Team. The sampling technique was taken in total (total sampling) or the full sampling technique of the Team of Tassel SSB School FC junior, which amounted to 16 people. The results of the correlation of the SSB Rumbai FC School Team where the first analysis between leg muscle power X1 and Y where rtab at a significant level ɑ (0.05) = rhitung 0,880) >rtabel (0.514), means that the hypothesis is accepted and there is a strong relationship between leg muscle power to Junior SSB Rumbai School Team's long passing ability. From the calculation of the analysis of both X2 and Y, where at a significant level ɑ (0.05) = berarti rhitung (0,630) > rtabel (0.514), it means that the hypothesis is accepted and there is a strong relationship between eye and foot coordination on the junior passing ability of the FC SSB Rumbai School Team. The third analysis of the relationship of leg muscle power (X1) eye and foot coordination (X2) with gastric passing results (Y) where rtab at a significant level ɑ (0.05) = rhitung 0,868) > rtabel (0.514), it can be concluded that the relationship between (X1) and (X2) with (Y) or the relationship of leg muscle power and eye and foot coordination with the results of hull passing at a strong interpretation.Key Words: Muscle Power, Gastric Coordination and Passing.